2012
DOI: 10.1186/1749-8104-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Midline crossing is not required for subsequent pathfinding decisions in commissural neurons

Abstract: BackgroundGrowth cone navigation across the vertebrate midline is critical in the establishment of nervous system connectivity. While midline crossing is achieved through coordinated signaling of attractive and repulsive cues, this has never been demonstrated at the single cell level. Further, though growth cone responsiveness to guidance cues changes after crossing the midline, it is unclear whether midline crossing itself is required for subsequent guidance decisions in vivo. In the zebrafish, spinal commiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…It also highlights the requirement of Netrin1 function in the presence of the Robo2-mediated repulsion. Finally, it is interesting to note that a previous study showed that Dcc promotes ventral growth of zebrafish spinal cord commissural primary ascending neuron axons through inhibition of Robo2 (Bonner et al, 2012). Therefore, the interaction between the Robo2-Slit and the Dcc-Netrin1 signaling pathways may play roles in a variety of guidance choice mechanisms in the CNS.…”
Section: Axonal Projection Patterns Of Adt Neurons Are Heterogeneousmentioning
confidence: 91%
“…It also highlights the requirement of Netrin1 function in the presence of the Robo2-mediated repulsion. Finally, it is interesting to note that a previous study showed that Dcc promotes ventral growth of zebrafish spinal cord commissural primary ascending neuron axons through inhibition of Robo2 (Bonner et al, 2012). Therefore, the interaction between the Robo2-Slit and the Dcc-Netrin1 signaling pathways may play roles in a variety of guidance choice mechanisms in the CNS.…”
Section: Axonal Projection Patterns Of Adt Neurons Are Heterogeneousmentioning
confidence: 91%
“…mRNA probes for islet, gata, and vsx families label specific post-mitotic neurons of consistent position and number within each spinal cord hemisegment 6 . In addition, axon guidance receptors such as those in the robo family are expressed in restricted populations of postmitotic neurons ( Figure 2C) 2,7,8 . Lateral mounting of embryos allows accurate counts of post-mitotic neurons.…”
Section: Representative Resultsmentioning
confidence: 99%
“…They branch, cross the midline, and exit both the dorsal and ventral spinal cord. When coupled with confocal laser scanning microscopy, these varied cellular behaviors are evident in laterally mounted embryos, using immunocytochemistry and genetically encoded fluorescent proteins such as GFP 2 . In Figure 2D, znp-1 immunocytochemistry was used to label developing motoneurons.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations